Courtage, compensation et reproduction de la décharge - Mohammed Benidir (Revue Internationale de Politique de Développement)
Collective reparation for the areas affected by the presence of secret detention centers during the « lead years » (1992-2002) and the development of the areas affected by mining are two programs initiated in the framework of associative seminars organized respectively in 2004 and 2012 in Zagora in South East Morocco. The compensation for the collective harm that the communities living near the centers and the sites of exploitation are the subject encourages to questioning the reproduction of the discharge through associative brokers and notables. The present article demonstrates that the localization of the compensation contrasts the rise in generality for the former and the descent in particularity for the latter. It analyzes how these contrasts give meaning to the evaluation of collective prejudices by the state, the mining company, the brokers, the notables and the militants. In addition to compensating the affected communities, it sifts the analysis the retributions that these actors themselves draw in return for the discharge and finally those that the State and the holding company withdraw in its policy defended by the latter.